2016
DOI: 10.1021/acssuschemeng.6b00230
|View full text |Cite
|
Sign up to set email alerts
|

Induced Tannin Adhesive by Boric Acid Addition and Its Effect on Bonding Quality and Biological Performance of Poplar Plywood

Abstract: Quebracho tannin wood adhesive in non-formaldehyde approach has low hardening rate and needs more pressing time than formaldehyde-based wood adhesives during wood composites production. In this study, boric acid (BA) was used to increase autocondensation rate of tannin to make poplar plywood. The main ingredients of the adhesives included quebracho tannin, NaOH, hexamine, BA and polymeric isocyanate (PMDI). Thermomechanical analysis of without BA adhesives showed that maximum modulus of elasticity increased wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 20 publications
1
32
0
Order By: Relevance
“…Boric acid cross-linker for PVA adhesives have shown enhanced thermal, mechanical and adhesive performance properties [ 31 ]. In addition to enhancing mechanical and adhesion properties, it was found that boric acid can be a preservative to tannin-based wood adhesive against fungal attack [ 32 , 33 ]. Boric acid forms strong bonds with free hydroxyl groups due to presence of vacant d-orbital in boron, which causes it to react with various nucleophiles to form complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Boric acid cross-linker for PVA adhesives have shown enhanced thermal, mechanical and adhesive performance properties [ 31 ]. In addition to enhancing mechanical and adhesion properties, it was found that boric acid can be a preservative to tannin-based wood adhesive against fungal attack [ 32 , 33 ]. Boric acid forms strong bonds with free hydroxyl groups due to presence of vacant d-orbital in boron, which causes it to react with various nucleophiles to form complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Additives can effectively solve the problems of tannin resin hydrophobicity and formaldehyde release and can improve the physical and mechanical properties, especially weather resistance, of the final wood products. Plywood products assembled with modified tannin resin adhesives meet the demand of exterior-grade plywood, have better properties than plywood assembled using phenolic resin, and have a certain commercial potential [26][27][28][29][30].…”
Section: Plywoodmentioning
confidence: 99%
“…The thermomechanical analysis curves have shown in Figure 2, which show the variation of Young's modulus E (MOE) as a function of curing temperature [7,23] . A higher MOE is obtained by increasing the proportion of GDE, with the highest MOE being almost 7100 MPa when the ratio of tannin/GDE is 1:1, with the MOE becoming 5300 MPa and 4800 MPa for tannin/GDE-2/1 and tannin/GDE-3/1, respectively.…”
Section: Thermomechanical Analysis (Tma)mentioning
confidence: 99%
“…Therefore, low or no aldehyde tannin adhesives have been developed by a number of approaches. Hexamethylenetetramine (hexamine) [22,23] , glyoxal [24] , furfuryl alcohol [25] , polymeric diphenylmethane diisocyanate (p-MDI) [23,26] , poly-ethylenimine (PEI) [27] , as well as carbohydrates-generated non-toxic and non-volatile aldehydes by specific oxidation [28] , were used to react with different condensed tannins to produce tannin-based wood adhesive without any kinds of volatile and toxic aldehydes. Certainly, some tannin wood adhesives were obtained though biomass resources (starch) mixing with condensed tannin, and alternative aldehydes acting as cross-linkers, leading to low formaldehyde emission [13,[29][30][31] .…”
Section: Introductionmentioning
confidence: 99%